Micropsalliota globovelveta sp. nov., from subtropical regions of China - Liu, Yu-Tong; Ding, Ling; Zeng, Hui; Wang, Sheng-Nan; Yan, Jun-Qing (Phytotaxa, 2025)
A new species, Micropsalliota globovelveta, collected in the subtropical regions of China, is described in this paper. It is characterized by very small basidiomata; reddish white to greyish rose pileus, covered with very short velvety fibrils; basidiospores 5.5–6.0 × 3.0–3.5 μm; tibiiform cheilocystidia; and velvety fibrils on the pileus composed of abundant globose to ovoid cells, with pale brown vacuolar pigment. The unique taxonomic status of the new species is verified by their placement in the phylogenetic trees based on four loci (ITS, LSU, rpb2, and tef1-α). Comprehensive descriptions, illustrations, and phylogenetic analysis results of the new species are provided, ensuring a complete understanding of this new species. Additionally, a key to 36 species of Micropsalliota in China is included to facilitate identification.